Effects of bariatric surgery on breast density in adult obese women: systematic review and meta-analysis - Sun, Dezheng; Huang, Zhiping; Dong, Wenyan; Zhao, Xiang; Liu, Chaoqian; Sheng, Yuan (Frontiers in Immunology, 2023)
Background: Bariatric surgery is one of the most effective methods for treating obesity. It can effectively reduce body weight and reduce the incidence of obesity-related breast cancer. However, there are different conclusions about how bariatric surgery changes breast density. The purpose of this study was to clarify the changes in breast density from before to after bariatric surgery. Methods: The relevant literature was searched through PubMed and Embase to screen for studies. Data on breast density scoring methods, density grades, and evaluation indicators from before to after bariatric surgery were collected, and meta-analysis was used to clarify the changes in breast density from before to after bariatric surgery. Result: A total of seven studies were included in this systematic review and meta-analysis, including a total of 535 people. The average body mass index decreased from 45.3 kg/m2 before surgery to 34.4 kg/m2 after surgery. By the Breast Imaging Reporting and Data System score, the proportion of grade A breast density from before to after bariatric surgery decreased by 3.83% (183 vs. 176), grade B (248 vs. 263) increased by 6.05%, grade C (94 vs. 89) decreased by 5.32%, and grade D (1 vs. 4) increased by 300%. There was no significant change in breast density from before to after bariatric surgery (OR=1.27, 95% confidence interval (CI) [0.74, 2.20], P=0.38). By the Volpara density grade score, postoperative volumetric breast density increased (standardized mean difference = -0.68, 95% CI [-1.08, -0.27], P = 0.001). Conclusions: Breast density increased significantly after bariatric surgery, but this depended on the method of detecting breast density. Further randomized controlled studies are needed to validate our conclusions.